2008
DOI: 10.1002/jcla.20244
|View full text |Cite
|
Sign up to set email alerts
|

Viral loads of cerebrospinal fluid in infants with enterovirus meningitis

Abstract: For a better understanding of the role of the viral load, free radicals, and cytokines in viral meningitis, we surveyed cerebrospinal fluid (CSF) obtained from patients below 1 year of age who showed positive for enterovirus. In their first examinations interleukin (IL)-6 and free radicals increased whereas pleocytosis was rarely observed. IL-6 decreased within the short period. Viral loads and free radicals increased simultaneously. IL-6 and free radicals of CSF are helpful for diagnosis and treatment of vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
(8 reference statements)
1
16
0
2
Order By: Relevance
“…2). This finding was confirmed by previously published studies demonstrating that the viral loads ranged from 3.1 to 4.6 log 10 copies/ml of CSF in HEV CNS infections (9,18,24).…”
Section: Discussionsupporting
confidence: 87%
“…2). This finding was confirmed by previously published studies demonstrating that the viral loads ranged from 3.1 to 4.6 log 10 copies/ml of CSF in HEV CNS infections (9,18,24).…”
Section: Discussionsupporting
confidence: 87%
“…This observation is relevant because detection of CSF pleocytosis is an important biochemical marker of meningitis in the clinical practice. Although there have been a few reports of young infants and children with no CSF pleocytosis during EV meningitis, the clinical and laboratory characteristics of these children have not been well documented, especially not in those beyond the neonatal age [1,3,6,8,9,11,12,17,18,20,24,28]. The mechanism to explain the lack of pleocytosis in some patients during EV meningitis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al suggested that young infants with EV meningitis and no CSF pleocytosis may be at an initial stage of illness when, though production of (pro) inflammatory cytokines has been stimulated, the blood leukocytes have not yet infiltrated the cerebrospinal cavity [22]. Kawashima et al observed that only 4 out of 21 patients with EV meningitis had CSF pleocytosis, despite high levels of the inflammatory cytokine, interleukin IL-6, in the CSF at presentation [12]. This may explain the significantly lower WBC count and higher CRP levels in patients with no CSF pleocytosis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A higher viral load was not associated with more severe disease 25. Younger children may have higher viral loads than older children 25. The CSF EV viral load currently has no clinical utility.…”
Section: Is the Ev Viral Load In Csf Important?mentioning
confidence: 91%
“…A study that measured the EV CSF viral load in 21 children under 1 year old with a clinical diagnosis of meningitis/encephalitis found it ranged from 241 to 22 468 copies/μL 25. A higher viral load was not associated with more severe disease 25.…”
Section: Is the Ev Viral Load In Csf Important?mentioning
confidence: 99%